Identification and Analysis of Chemical Constituents and Rat Serum Metabolites in Lycopodium clavatum Using UPLC-Q-TOF/MS Combined with Multiple Data-Processing Approaches. (2nd July 2019) - Li, Xin; Kang, Mingqin; Ma, Ningning; Pang, Tan; Zhang, Yanjun; Jin, Hua; Yang, Zhen; Song, Lili
Abstract : Lycopodium clavatum is a dry whole grass of Lycopodium japonicum Thunb.; it has been extensively used to anti-inflammatory, antioxidant, and antimicrobial actions and inhibits acetylcholinesterase activity. However, it lacks further compounds research of Lycopodium clavatum in vivo and in vitro . In this work, a rapid method was established using the ultra high performance liquid chromatography with quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS) combined with multiple data-processing approaches for compounds analysis of Lycopodium clavatum in vitro and in vivo . Finally, 30 peaks were characterized in 75% ethanol extract of Lycopodium clavatum and 17 peaks were characterized in rat plasma that including 12 prototype compounds and 5 metabolites. Methylation and demethylation are the main transformation reactions of Lycopodium clavatum in rat serum. This work could be helpful for understanding the complex compounds of Lycopodium clavatum and further analyzing the pharmacological studies of active compounds.